Slope stability analysis of coastal geotechnical structures under combined effects of earthquake and rainfall - Jia, Yuyue; Luan, Shuyang; Asheghabadi, Mohsen Saleh; Xing, Dongliang; Yuan, Hang; Liu, Junwei (Frontiers in Earth Science, 2024)
A study was conducted to analyze the stability of coastal geotechnical slopes under the combined influence of rainfall and earthquakes, considering the geological conditions and characteristics of these slopes in coastal areas. The results indicate that, under the same seismic acceleration amplitude, the shear strength of the slope soil gradually decreases as the water content increases, resulting in a decrease in the stability coefficient. Similarly, with a constant water content in the slope, an increase in seismic acceleration amplitude leads to heightened soil shear stress, consequently decreasing the stability coefficient. Maintaining constant water content while increasing seismic acceleration results in elevated soil shear stress, reduced shear strength, and a subsequent decrease in the stability coefficient. The simultaneous occurrence of intense rainfall and a strong earthquake pushes the slope to its most precarious state, causing the most significant reduction in the stability coefficient.Incorporating anti-slip piles substantially enhances the slope's stability coefficient, and an optimal arrangement of anti-slip piles for the most unfavorable conditions is proposed.